If f ( x ) = 1 6 x + 3 , what is the value of f − 1 ( 3 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thank you...
Relevant wiki: Inverse Functions
f ( x ) = y = 1 6 x + 3
f − 1 ( y ) = x = 1 6 y − 3
f − 1 ( x ) = 1 6 x − 3
f − 1 ( 3 ) = 1 6 3 − 3 = 0
Relevant wiki: Inverse Functions
f − 1 ( 3 ) = x ⟹ f ( x ) = 3 ⟹ 1 6 x + 3 = 3 ⟹ 1 6 x = 0 ⟹ x = 0
That’s how I solved it too!
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Inverse Functions
f ( x ) = 1 6 x + 3 To get f − 1 ( x ) just change x to f − 1 and f(x) to x x = 1 6 f − 1 ( x ) + 3 x − 3 = 1 6 f − 1 ( x ) f − 1 ( x ) = 1 6 x − 3 f − 1 ( 3 ) = 1 6 3 − 3 = 1 6 0 = 0